Trumpet repertoire: a report on trumpet solo literature by Bitsch, Hovhaness, Ketting, and Haydn - Johnson, Lucas (Kansas State University, 2018)
LUCAS CHARLES JOHNSON Trumpet Repertoire: A Report on the Trumpet Solo Literature by Bitsch, Hovhaness, Ketting, and Haydn (Under the direction of JIM JOHNSON) This report provides analysis of Marcel Bitsch’s Quatre Variations sur un Theme de Domenico Scarlatti, Alan Hovhaness’ Prayer of Saint Gregory, Otto Ketting’s Intrada, Joseph Haydn’s Concerto for Trumpet in E-flat Major. This report contains four chapters, one devoted to each piece. Chapters include the composer’s biographical information, historical significance (if applicable), theoretical analysis, and performance considerations.
Keywords: Trumpet; Bitsch; Hovhaness; Ketting; Haydn